MOTIVASI MASYARAKAT BERMUKIM DI KAWASAN RAWAN BENCANA BANJIR - Aulia Rahma; Djoko Abi Suroso; Lutfi Setianingrum (Jurnal Perencanaan dan Pengembangan Kebijakan, 2023)
Rajabasa sub-district is one of areas prone to flooding due to the overflow of Way Kandis River. However, there are still many people who live in the flood-prone area for various reasons. This study aims to determine the motivation of people living in flood-prone areas located in Rajabasa sub-district, Bandar Lampung City. The method used is inductive qualitative. The data in the study were obtained by semi-structured interviews with the people of Rajabasa Village who were directly affected by the flood disaster. The data analyzed using induction resulted in a concept related to the motivation of the people to live. Based on the findings of the concepts generated from the research, the motivations of the dweller in flood-prone areas in the Rajabasa sub-district are 1) The lack of options to live in urban areas due to family legacy and nothing land ownership elsewhwere, resulting the acceptance of flooding by the residents; 2) A sense of security with the community that they do not feel threatened and are used to flood disasters; 3) Affordable accessibility of the area which reached by public transportation and connects with schools and workplaces; 4) A sense of comfortable since they have been settled for a long time in the area.